(untitled) (London Journal of Medical and Health Research, 2026)
Aging is a multifactorial biological process driven by progressive declines in cellular energy production, hormonal signaling, and immune regulation. While advances in geroscience have identified key molecular hallmarks of aging, translation into practical, clinician-friendly frameworks remains limited. Current medical approaches often address metabolic, endocrine, and inflammatory dysfunction in isolation, which may fail to capture the interconnected biology underlying accelerated aging and chronic disease. The Longevity Triadis presented as a systems-based clinical framework integrating three interdependent pillars—mitochondrial resilience, hormonal orchestration, and inflammation modulation—to guide precision longevity care. Mitochondria regulate cellular energy availability, redox balance, and stress adaptation; hormonal networks coordinate metabolism, reproduction, and tissue repair; and chronic low-grade inflammation acts as a central accelerator of biological aging. Dysregulation in any one pillar can destabilize the others, creating self-reinforcing feedback loops that promote metabolic decline, immune dysfunction, and reduced physiologic reserve. This manuscript synthesizes emerging mechanistic and clinical evidence linking the Longevity Triadto established hallmarks of aging and demonstrates its application through case-based clinical examples. Diagnostic strategies including functional metabolic testing, comprehensive endocrine assessment, inflammatory and immune biomarkers, and lifestyle-related exposure evaluation are discussed. Targeted interventions—encompassing lifestyle modification, nutritional and micronutrient support, exercise prescription, and individualized hormonal optimization—are illustrated to show how coordinated, multi-pillar treatment can restore physiologic balance and improve patient-centered outcomes. The Longevity Triad offers a practical, integrative roadmap for clinicians seeking to move beyond symptom-based management toward systems-level, personalized strategies that support healthy aging, metabolic flexibility, and long-term resilience.